2005
DOI: 10.1128/mcb.25.9.3535-3542.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of CtIP Leads to Early Embryonic Lethality Mediated by G1 Restraint and to Tumorigenesis by Haploid Insufficiency

Abstract: CtIP interacts with a group of tumor suppressor proteins including RB (retinoblastoma protein), BRCA1, Ikaros, and CtBP, which regulate cell cycle progression through transcriptional repression as well as chromatin remodeling. However, how CtIP exerts its biological function in cell cycle progression remains elusive. To address this issue, we generated an inactivated Ctip allele in mice by inserting a neo gene into exon 5. The corresponding Ctip ؊/؊ embryos died at embryonic day 4.0 (E4.0), and the blastocysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
130
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 46 publications
(65 reference statements)
14
130
2
1
Order By: Relevance
“…More importantly, it has been shown that inactivation of CtIP in mice leads to early embryonic lethality, and the life span of Ctip +/À heterozygotes, which have Ctip haploid insufficiency, was shortened due to the development of multiple types of tumors. These findings show that CtIP is a critical protein in early embryogenesis and implicates an important role of CtIP in tumorigenesis (39). In addition, CtIP interacts with the BRCT domains of BRCA1 where most mutations occur in BRCA1 breast cancer patients, and such protein-protein interaction is abolished by tumorassociated mutations in the BRCT domains (26,29,31), suggesting that interaction between CtIP and BRCA1 is of functional relevance in the breast cancer suppressor activity.…”
Section: Discussionmentioning
confidence: 76%
“…More importantly, it has been shown that inactivation of CtIP in mice leads to early embryonic lethality, and the life span of Ctip +/À heterozygotes, which have Ctip haploid insufficiency, was shortened due to the development of multiple types of tumors. These findings show that CtIP is a critical protein in early embryogenesis and implicates an important role of CtIP in tumorigenesis (39). In addition, CtIP interacts with the BRCT domains of BRCA1 where most mutations occur in BRCA1 breast cancer patients, and such protein-protein interaction is abolished by tumorassociated mutations in the BRCT domains (26,29,31), suggesting that interaction between CtIP and BRCA1 is of functional relevance in the breast cancer suppressor activity.…”
Section: Discussionmentioning
confidence: 76%
“…It is also involved in the transcriptional repression by the Rb family possibly by recruitment of CtBP and associated HDACs (reviewed by Chinnadurai, 2006b). It has recently been shown that knockout mice, which do not express CtIP die at an early stage of development, probably due to aberrant cell cycle regulation (Chen et al, 2005). It has been surmised that CtIP expression is necessary for correct phosphorylation of Rb and subsequent cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…The CtIP/CtBP complex plays a role in E2F/Rb-mediated repression and it has been suggested that AdE1A could alleviate this repression through dissociation of the complex (Meloni et al, 1999). Furthermore, it is possible that AdE1A can directly affect CtIP's ability to regulate Rb-dependent S-phase entry, perhaps by controlling its phosphorylation (Chen et al, 2005) (Figure 9). Moreover, CtIP's phosphorylation-dependent association with BRCA1 regulates the G2/M transition checkpoint following DNA damage (Yu and Chen, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations